Health Counseling on Smoking Behavior and Drug Use as an Effort to Improve the Health Status of the Community - Najihah; Taqiyah, Yusrah (Window of Community Dedication Journal, 2020)
Adolescence is a transitional period from childhood to adulthood that experiences the development of all aspects / functions to enter adulthood. The changes experienced by adolescents, both physical changes and psychosocial changes, can lead to various adolescent health problems. Adolescent health-related problems can include reproductive health, infectious diseases caused by personal and environmental hygiene, accidents, obesity, anemia, smoking behavior, drinking alcohol, free sex and drug use. These health problems can be prevented, and the form of prevention is with health promotion efforts that can be done with health counseling to improve the degree of public health, especially adolescent groups. The counseling material presented was about smoking behavior and drug use. This activity was carried out at the Wihadatul Ulum YW-UMI Islamic Boarding School in Bontokassi Village using lecture and discussion methods. The result of this activity is that students understand about the dangers of smoking behavior with drug use, where 90% of students are able to answer questions given after health counseling. In addition, students participated in the activity with enthusiasm so that it is hoped that with the increase in student knowledge they can become change agents in the school environment, family and community to improve health status.